Catturare la realtí per la progettazione BIM In edilizia e nelle infrastrutture - Giovanni Perego (mediaGEO soc. coop., 2020)
The technological advances of the last few years are revolutionizing the panorama of what for decades was called topographic survey. Today, from the individual points surveyed and then returned one by one in the traditional topographic survey, millions of points have been obtained in a few minutes, grouped in real clouds that can be mounted one on top of the other, for the complete return of the relief. Clouds of points that are usually already covered, on their surface, by the photographic image, which provides additional important information on the materials and characteristics of the detected objects. A profound transformation is underway, which is why I think it is more correct to define the contemporary importance of "capturing reality". The significant progress we are talking about is making a decisive contribution to the digitalization of the design processes, which we are all used to defining BIM, which we are also adopting in Italy, thanks also to the 2017 decree, which courageously introduced its mandatory use. in public procurement, by decreasing thresholds from year to year until 2025, when it will always be mandatory. BIM requires the use of three-dimensional models rich in associated information, and therefore of much more complex, detailed and precise findings than previously occurred. So the availability of new relevant technologies arrives at the right time, and at the same time offers a great stimulus for the introduction of BIM in design and construction.